Öğrenci mikroskobunda epifloresan görüntüleme - Gökduman, Selcen Necibe (Institute of Electrical and Electronics Engineers Inc., 2020)
Fluorescence microscopy is used as an important tool for research and education in the biological sciences. Fluorescence microscopes allow fluorescent signal to be obtained by stimulating markers in biological samples using light at a certain wavelength. The high cost of fluorescence microscopes has limited its use to academic laboratories and wealthy research institutions. In this project, a low-cost and accessible epifluorescence imaging device has been produced. A plug-in device has been designed to be used to achieve fluorescence imaging without changing the optical elements of the existing standard student microscope. The built device is designed to be mounted on the eyepiece of a monocular student microscope to obtain an epifluorescence image. In this way, it is aimed to make fluorescence imaging accessible for many laboratories with a device that can be mounted as needed on an easily available student microscope.
Epifluorescnce imaging on a student microscope
Keywords: Epifloresan Görüntüleme; Öğrenci; Microscope; Epifluorescnce Imaging; Student; Microscope